2016
DOI: 10.1080/15267431.2016.1215316
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Sibling Maintenance Behavior Expectations and Perceptions in the Relationship Between Family Communication Patterns and Relationship Satisfaction

Abstract: Sibling relationships are influenced both by the behaviors performed within the relationship (e.g., relational work; Myers et al., 2001) and by the family system as a whole (White & Klein, 2008). This study extends family communication patterns theory (FCP) by examining whether communicative relationship maintenance plays a role in the relationship between FCP and sibling relationship satisfaction. Data from 327 adult siblings from across the United States tested using Hayes (2013) PROCESS revealed that conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
13
0
3
Order By: Relevance
“…Furthermore, children’s changes in residential location outside of the family household may render referential interactions, specifically shared tasks and networks, less relevant (Morr Serewicz et al, 2007). The parent–child communication environment, however, clearly remains important during emerging adulthood (Dorrance Hall & McNallie, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, children’s changes in residential location outside of the family household may render referential interactions, specifically shared tasks and networks, less relevant (Morr Serewicz et al, 2007). The parent–child communication environment, however, clearly remains important during emerging adulthood (Dorrance Hall & McNallie, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Baxter and Pederson (2013) found that children’s perceived conversation orientation was positively associated with children’s satisfaction in parent–child relationships; children’s perceived conformity orientation was not significantly related to relationship satisfaction. In addition, Dorrance Hall and McNallie (2016) established a link between parent–child conversation orientation and satisfaction within sibling relationships. The limited findings suggest that conversation orientation corresponds with better relational health.…”
Section: Family Communication Orientationsmentioning
confidence: 99%
“…SEM was chosen because this technique is a type of multivariate statistical analysis that can handle the relationship of several explanatory variables despite multicollinearity. The advantages of this method include being immune or robust, not requiring various assumptions or conditions, being suitable for all types of data scales and not requiring a large number of samples (Hair, Black, Babin and Anderson, 2010). Figure 1 explains that the main issue discussed in this study is the quality of the relationship between parents and children with autism.…”
Section: Methodsmentioning
confidence: 99%
“…People with higher conversation orientation report less anxiety (Ledbetter & Schrodt, 2008). Conversation orientation is also positively associated with closeness between family members (Afifi & Olson, 2005) and young adults’ family satisfaction (Baxter & Pederson, 2013), and relationship satisfaction among siblings (Dorrance Hall & McNallie, 2016). Research is less clear about how conformity orientation affects well-being.…”
Section: Family Communication Patternsmentioning
confidence: 99%